The relationship of macroeconomic variables and lapsation of life insurance policies - Lim, Chee Chee (2000)
Lapsation refers to the discontinuation of insurance policies due to non-payment of premiums by policyhoders. The phenomenon of lapsation, especially for life insurance policies, has always been a worldwide concern.Malaysia is not spared of this phenomenon.This study was therefore undertaken to explore and examine the relationship of certain macroeconomic variables, such as (a) percapita income, (b) umemployment, (c)inflation, (d)market return and (e) real interest rate, against the lapsation of life insurance policies in the Malaysian context.The sources of this study were secondary in nature.They comprised of data published in the Annual Report of the Insurance Commissioner (1963-69),the Annual Report of the Director General of Insurance (1970-99) and the Economic Report (1977/78-98/99).A sample size of 22 years has been included in this study and the time frame for this study ranged from 1977 to 1998.The 0.05 level of significance was used as the critical level for decision-making regarding the hypothesis.The major finding of this study indicated that the R-squared (R2) was 0.655.With the significance level of p<0.05, the F-statistic of 6.077 was significant at the 0.002 level.This means that 65.5 percent of the variance in the lapsation of life insurance policies has been significantly explained by the five macroeconomic variables: (a) per capita income, (b) unemployment, (c) inflation, (d)market return and (e) real interest rate jointly.Nevertheless, a close examination of the results showed that unemployment appeared to have the highest number of beta (0.720) and was the only macroeconomic variable (independent variable)found to be significant (p=0.035)in explaining the variance of the lapsation of life insurance policies.Meanwhile, the positively related which means low employment will help in reducing the lapsation of life insurance policies.